Student and Teacher Responses to Printed Textbooks as Learning Resources for the Indonesian Language in the Digital Learning Era - Aditya, Mansyur Rohmat; Sufanti, Main (Universitas Muhammadiyah Surakarta, 2023)
In the contemporary digital learning landscape, the role of printed textbooks as educational resources remains a topic of interest and scrutiny. This study investigates the perceptions and utilisation of printed textbooks among students and teachers in the context of Indonesian language learning. Through a qualitative approach employing interviews and surveys, the study examines the nuanced attitudes towards printed textbooks amidst the proliferation of digital learning tools. Findings reveal the enduring value attributed to printed textbooks by both students and teachers, despite the advent of digital resources. Moreover, the study sheds light on the specific contexts in which printed textbooks are deemed advantageous or preferable over digital alternatives. This research contributes to a deeper understanding of the evolving dynamics between traditional printed materials and digital learning platforms within contemporary educational settings.